Peran Guru dalam Deteksi Dini Tumbuh Kembang Anak Usia Dini di RA Arrahmah - Najwa Dwi Aprillia; Nursyamsiah Simbolon; Putri Amelia; Dea Miftahul Jannah; Homsani Nasution (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Early childhood development screening is an important effort to ensure optimal development during a child's golden age, which includes physical, motor, language, cognitive, and socio-emotional aspects. Early Childhood Education (PAUD) teachers play a key role in implementing early detection, given their intensive interaction with children during learning activities. However, early detection in PAUD institutions faces challenges such as limited teacher competencies, non-standardized screening instruments, and suboptimal cross-sector collaboration. This study aims to examine the role of teachers in early childhood development screening at RA Arrahmah using a qualitative approach and case study. Data were collected through observations, in-depth interviews, and documentation with the head of RA and class teachers during October-November. The results show that teachers have carried out early detection in an integrated manner through continuous observations. However, the use of standardized screening instruments has not been optimal and still relies on informal observations. Major challenges include limited training, individual observation time, and the lack of a structured early detection program. This study concludes that strengthening teacher competencies, integrating early detection into institutional policies, and enhancing collaboration with parents and healthcare professionals are necessary to optimize early childhood development screening sustainably.